The investigation of lung fonctions in the workers of Malatya Tekel tobacco factory - Tecimer, Coskun; Ardic, Sadik; Pehlivan, Erkan; Yologlu, Saim; Ozdemir, Ramazan; Aladag, Murat; Ustun, Mukaddes (Annals of Medical Research, 2021)
None